The Human Resource Graduates’ Attributes: An Assessment - Stephanie Jan Khevan D. Javate; Joanna Mae M. Santos; Kristine J. Garcia; Troi J. Sacatrapos; Lalyn S. Federizo; Mary Joyce Anne C. Valino; Carolyn P. Gonzales-Marzan (Research Synergy Foundation, 2026)
This study examines the employability and professional attributes of Human Resource (HR) graduates in the Philippines. A quantitative descriptive-correlational method was used to evaluate alumni's perceptions of their competencies in areas such as communication, critical thinking, and information technology. Based on the findings, most of the respondents were female, aged between 20 and 25, single, graduates from batch 2018-2019, and regular private employees with 1-3 years in service. Results showed that while graduates feel highly proficient in soft skills and human relations, they demonstrate a lower mastery of specialized technical software. Surprisingly, the analysis found no statistically significant association between these academic attributes and actual employment status, suggesting that a degree alone does not guarantee a career. The researchers suggest that higher education institutions (HEIs) must collaborate more closely with the private sector to bridge the gap between classroom learning and industry demands.